Local Secretory Trafficking Pathways in Neurons and the Role of Dendritic Golgi Outposts in Different Cell Models - Wang, Jingqi; Fourriere, Lou; Gleeson, Paul A. (Frontiers in Molecular Neuroscience, 2020)
A fundamental characteristic of neurons is the relationship between the architecture of the polarised neuron and neural networking. Intracellular membrane trafficking is paramount to establish and maintain neuronal structure; perturbation in trafficking results in defects in neurodevelopment and neurological disorders. Given the physical distance from the cell body to the distal sites of the axon and dendrites, transport of newly synthesised membrane proteins from the central cell body to their functional destination at remote, distal sites represents a conundrum. With the identification of secretory organelles in dendrites, including endoplasmic reticulum and Golgi outposts, recent studies have proposed local protein synthesis and trafficking distinct from the conventional anterograde transport pathways of the cell body. A variety of different model organisms, including Drosophila, zebrafish and rodents have been used to probe the organisation and function of the local neuronal secretory network. Here, we review the evidence for local secretory trafficking pathways in dendrites in a variety of cell-based neuronal systems and discuss both the similarities and differences in the organisation and role of the local secretory organelles, especially the Golgi outposts. In addition, we identify the gaps in the current knowledge and the potential advances using human induced pluripotent stem cells in defining local membrane protein trafficking in human neurons and in understanding the molecular basis of neurological diseases.